Quantitative evaluation of the impact of the Healthy Communities Initiative in Cincinnati - Mattke, Soeren (Research report (Rand Corporation), 2014)
Metropolitan Cincinnati residents have traditionally had among the highest health care costs in the United States, yet little evidence exists that residents are getting their money's worth, especially in terms of preventive and primary care. Recently, large employers, health plans, and health care providers in the Cincinnati area joined with community organizations in an effort to improve health care and population health, as well as reduce health care costs by focusing on five priority areas: coordinated primary care, health information exchange, quality improvement, public reporting and consumer engagement, and payment innovations. Spearheaded by General Electric (GE) Cincinnati, the resulting Healthy Communities Initiative in Cincinnati was implemented in 2009. In 2012, GE asked RAND Health Advisory Services to assess progress over the first three years of the initiative. Overall, the findings were largely inconclusive because of a concomitant marketwide shift to high-deductible health policies (which are known to have profound effects on care-seeking behavior) and the early stage of the intervention. However, there were some encouraging signs that better care coordination bears fruit, such as less illness-related work loss and fewer avoidable hospital admissions and readmissions. These early impacts suggest that the initiative may succeed in improving care, lowering cost, and improving health status if given sufficient time.